A Cross-Cultural Study of Justice Sensitivity and Its Consequences for Cooperation. Issue 7 (September 2020) - Baumert, Anna; Maltese, Simona; Reis, Dorota; MacLeod, Colin; Tan-Mansukhani, Roseann; Galang, Adrianne John R.; Salanga, Maria Guadalupe C.; Schmitt, Manfred
In Western samples, individuals differ systematically in the importance they assign to matters of justice and injustice, and dispositional Justice Sensitivity can be differentiated according to the perspectives of victim, observer, beneficiary, and perpetrator. In a cross-cultural comparison between the Philippines, Germany, and Australia ( N = 677 students), we investigated whether Justice Sensitivity can be equivalently described by these four perspectives, whether measurement instruments have invariant psychometric properties, and whether the psychological relevance of the Justice Sensitivity perspectives for cooperation behavior differs between these cultural contexts. The results of multigroup confirmatory factor analyses support weak measurement invariance and invariant associations between Justice Sensitivity perspectives and trust game decisions. Across cultures, victim sensitivity predicted reluctance to cooperate under threat of exploitation, and observer, beneficiary, and perpetrator sensitivities predicted cooperation under temptation. Our study extends insight into Justice Sensitivity to underresearched cultural contexts of urban and rural Philippines.